Cyclic fatigue resistance of newly manufactured rotary nickel titanium instruments used in different rotational directions. (2nd May 2012) - Gambarini, Gianlucca; Gergi, Richard; Grande, Nicola Maria; Osta, Nada; Plotino, Gianluca; Testarelli, Luca
Abstract The aim of this study was to investigate whether cyclic fatigue resistance is increased for nickel titanium instruments manufactured with improved heating processes in clockwise or counterclockwise continuous rotation. The instruments compared were produced either using the R‐phase heat treatment (K3XF; SybronEndo, Orange, CA, USA) or the M‐wire alloy (ProFile Vortex; DENTSPLY Tulsa Dental Specialties, Tulsa, OK, USA). Tests were performed with a specific cyclic fatigue device that evaluated cycles to failure of rotary instruments in curved artificial canals. Results indicated no significant difference in resistance to cyclic fatigue when rotary nickel titanium instruments are used in clockwise or counterclockwise continuous rotation. In both directions of rotation, size 04‐25 K3XF showed a significant increase (P < 0.05) in the mean number of cycles to failure when compared with size 04‐25 ProFile Vortex.